Worldwide dynamic biogeography of zoonotic and anthroponotic dengue - Aliaga-Samanez, Alisa; Cobos-Mayo, Marina; Real-Giménez, Raimundo; Segura Moreno, Marina; Romero-Pacheco, David; Fa, Julia E.; Olivero-Anarte, Jesús (PLoS - Negl Trop Dis, 2021)
Dengue is a viral disease transmitted by mosquitoes. The rapid spread of dengue could lead to a global pandemic, and so the geographical extent of this spread needs to be assessed and predicted. There are also reasons to suggest that transmission of dengue from nonhuman primates in tropical forest cycles is being underestimated. We investigate the finescale geographic changes in transmission risk since the late 20th century, and take into account for the first time the potential role that primate biogeography and sylvatic vectors play in increasing the disease transmission risk. We apply a biogeographic framework to the most recent global dataset of dengue cases. Temporally stratified models describing favorable areas for vector presence and for disease transmission are combined. Our models were validated for predictive capacity, and point to a significant broadening of vector presence in tropical and non-tropical areas globally. We show that dengue transmission is likely to spread to affected areas in China, Papua New Guinea, Australia, USA, Colombia, Venezuela, Madagascar, as well as to cities in Europe and Japan. These models also suggest that dengue transmission is likely to spread to regions where there are presently no or very few reports of occurrence. According to our results, sylvatic dengue cycles account for a small percentage of the global extent of the human case record, but could be increasing in relevance in Asia, Africa, and South America. The spatial distribution of factors favoring transmission risk in different regions of the world allows for distinct management strategies to be prepared.
Keywords: Biogeografía; Dengue; Dengue; Rapid spread; Sylvatic dengue cycles; Transmission risk detection